Out-of-Class Speaking Anxiety among Indonesian EFL Students and Its Relationship with Self-Perceived Speaking Skills, Vocabulary Proficiency, and Gender - Daflizar, Daflizar (Journal of Languages and Language Teaching, 2024)
Speaking anxiety has always been an intriguing topic in the field foreign language education. While a plethora of studies have been conducted on this issue in the Indonesian context, most of them have focused on students’ English-speaking anxiety in the EFL classroom, with very few examining anxiety outside of the classroom. To bridge this gap, this study aimed to investigate levels of out-of-class speaking anxiety among Indonesian tertiary EFL students and examine the relationships between their self-perceived speaking skills, self-perceived vocabulary size, and anxiety. Additionally, the study sought to examine whether there was a significant difference in anxiety levels between genders. Using a quantitative approach, a survey was administered to 87 participants from three different institutions of higher education. The results showed that students experienced anxiety in various situations, with most being moderately anxious. A moderate negative correlation was observed between self-perceived speaking skills and anxiety, while a weak negative relationship was found between self-perceived vocabulary size and anxiety. The study also found that females exhibited higher anxiety levels than males. Practical implications for curriculum designers and teachers in the Indonesian context are put forward.